Lala Lieyana Enterprise / Marlie Dhazniel Rusli ... [et al.] - Rusli, Marlie Dhazniel; Saidan, Nur Delima; Che Amran, Mohd Izzat Syazwan; Sazali, Muhamad Harith Hazwan; Nor Fazli, Muhammad Redza Zikry (2021)
In December of 2018, Lala Lieyana Enterprise was founded. This business has been in existence for two years. No 756, Jalan Selasih 5, Taman Selasih, 09000 Kulim, Kedah Darul Aman is the company's address. The company focuses on producing food products like as biscuits, ‘kuih raya’, and chips, with Family Corner biscuits and cookies being the most popular. Mrs. Liyana is one of FC Rishfood Industries (M) Sdn Bhd’s stockists. The company is run by family members, and delivery is handled through agents. It began in Kedah and has since spread to the states of Pulau Pinang, Perak, Perlis, and Selangor. They run their business through E-commerce and have a Facebook page called CikLala (Lala lieyana). They market their product by posting six to seven times every day. Lala Lieyana Enterprise has no employees or staff. However, they do have more than 50 agents spread over the states. They also believe that delivering high-quality services, such as on-time delivery and delicious cuisine, is the most crucial financial success factor.